Cicatrização do cólon semi-obstruído de ratos após uso do sildenafil intraperitoneal ou oral - Joao Luis Oliveira Gusmao de Andrade (2012)
INTRODUCTION: Anastomosis held treatment in obstructed colon presents higher incidence of fistula, with increased post-operative morbidity and mortality. It is believed that this occurs due to changes in the wall of the bowel segment as edema or changes of microcirculation, and has been studied treatments which may reduce the deleterious effects of intestinal obstruction in healing of anastomosis. OBJECTIVE: To evaluate the healing of left colon in rats in presence of bowel obstruction after use of oral or topic sildenafil. METHODOLOGY: There were studied 17 females wistar rats distributed into three groups: untreated (n = 6), colonic obstruction, colonic resection, primary anastomosis; Sildenafil topic (n = 5), colonic obstruction, colonic resection, primary anastomosis and peritoneal irrigation with sildenafil at the end of surgery; Oral Sildenafil (n = 6), colonic obstruction, colonic resection and primary anastomosis, administration of oral sildenafil by gastric gavageat the end of surgery. The colonic obstruction was done through colonic ligation with 2-0 silk against a catheter with the goal of creating an abrupt narrowing of colonic lumen, allowing passage of gas. After 24 hours, there was made resection of the silk-ligated area and held the colonic anastomosis. The animals were killed on the seventhday after the anastomosis and evaluated for the presence of the fistula, burstingpressure and angiogenesis at microscopy. RESULTS: The groups that have received sildenafil IP and VO presented increase in bursting pressure when compared with untreated group. There was also increased angiogenesis in animals treated with sildenafil IP when compared to animals not treated and the group treated with sildenafil VO. CONCLUSION: The use of sildenafil was able to stimulate the healing of obstructed colon in rats.